Dermatology consultations significantly contribute quality to care of hospitalized patients: a prospective study of dermatology inpatient consults at a tertiary care center. (3rd June 2016) - Galimberti, Fabrizio; Guren, Lauren; Fernandez, Anthony P.; Sood, Apra
Abstract: Background: Cutaneous abnormalities are common in hospitalized patients but are frequently missed or misdiagnosed by admitting teams. Inpatient dermatology consultations provide important information to help diagnose and manage these patients. However, few studies have analyzed dermatology inpatient consultations and their effect. Methods: We prospectively collected information for 691 consecutive dermatology consultations from November 2013 to November 2014. Results: Patients ranged in age from newborns to 97 years old. The internal medicine service requested the most consultations (45%). Only 6.5% of consultations were requested within 24 hours of appearance of cutaneous findings. Before consultation, 70.3% of patients did not receive treatment for or based on their cutaneous findings. Dermatology consultation resulted in treatment change in 81.9% of patients. The most common diagnoses were drug rash and contact dermatitis. Biopsies confirmed 71.7% of the initial bedside diagnoses by the dermatology consultation team. Conclusions: Common skin diseases were responsible for the majority of dermatology consultations. Most patients were not treated for their cutaneous conditions before the dermatology consultation. Dermatology consultations resulted in treatment changes in the majority of cases.